Development of Magic Cube Learning Media to Enhance Students: Conceptual Understanding of Number Patterns - Abelia Chaerani; Dewi Nurul Lathifah; Dea Gusera Andini; Abdi Gusti Nagara; Elsa Susanti; Zulkardi; Budi Mulyono; Meryansukmayeka Meryansukmayeka (Universitas Sriwijaya, 2025)
This study aims to develop the Magic Cube, an innovative manipulative learning medium designed to improve students’ conceptual understanding of number patterns. Number patterns are essential for building mathematical reasoning and problem-solving skills, yet many students struggle due to abstract teaching methods that lack interactive components. Previous studies have highlighted the effectiveness of game-based learning, but there remains a research gap in developing tangible and engaging media that directly support students’ comprehension. To address this, the study applied a Research and Development (R&D) approach using the ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation. The Magic Cube, designed as a three-dimensional cube equipped with material and question cards, was validated by two media experts and two material experts, achieving validity scores of 86% and 73%. Practicality tests involving teachers and students resulted in scores of 84.83% and 86.6%, respectively. Furthermore, pre-test and post-test results showed a significant improvement in students’ conceptual understanding, with an N-Gain score of 0.7, categorized as high. These findings indicate that the Magic Cube is a valid, practical, and effective instructional tool. The study contributes to enhancing interactive mathematics learning and provides broader implications for fostering active engagement and improving students’ comprehension of abstract mathematical concepts.